Mixed Invasive Apocrine Papillary/Micropapillary Carcinoma of the Breast: Another Brick in the Triple-Negative Wall. (June 2021) - Cima, Luca; Mirabassi, Nicola; Sartori, Chiara; Carbone, Francesco Giuseppe; Morelli, Luca; Cserni, Gábor; Barbareschi, Mattia
Pure invasive papillary carcinoma (IPC) is a rare subtype of breast carcinoma with good prognosis compared with classical invasive breast carcinoma (IBC) of no special type. The majority of IPC are estrogen receptor and progesterone receptor (ER/PR) positive and HER2 negative (luminal A-like). We report the case of a 72-year-old women who was referred to the Senology Clinic for a routine workup following surgery for an intraductal papilloma. The core needle biopsy (CNB) showed a lesion mainly composed of irregular papillae and micropapillae with apocrine epithelial cells of low-to-intermediate nuclear grade, without a myoepithelial cell layer within the papillae and at the periphery, as demonstrated with multiple immunostains. The diagnosis of apocrine papillary lesion of uncertain malignant potential was made. The subsequent lumpectomy showed an IBC with the same cyto-architectural features as the CNB. In addition, lymphovascular invasion and papillary/micropapillary apocrine in situ lesion were noted. Notably, the tumor was ER/PR and HER2 negative and strongly positive for androgen receptor. A final diagnosis of mixed apocrine papillary/micropapillary carcinoma with triple-negative status was made. To the best of our knowledge, this is the first report of an IBC with these features. Breast pathologists should be aware of this entity when dealing with CNB samples characterized by a complex papillary lesion with apocrine atypia that lacks a myoepithelial cell layer on multiple immunostains. These lesions should be classified at least as of uncertain malignant potential based on the cyto-architectural features prompting a surgery for removal.